Catalytic properties of mesoporous Al–La–Mn oxides prepared via spray pyrolysis. (October 2016) - Kim, Goun; Jung, Kyeong Youl; Lee, Choul-Ho; Han, Jeong-Sik; Jeong, Byung-Hun; Park, Young-Kwon; Jeon, Jong-Ki
Graphical abstract: Highlights: Al–La–Mn oxides were prepared using spray pyrolysis. Al–La–Mn oxides exhibit large and uniform pore sizes. Mesoporous Al–La–Mn oxides were compared with those prepared by conventional precipitation. Mesoporous Al–La–Mn oxides show superior activity in decomposition of hydrogen peroxide. Abstract: Mesoporous Al–La–Mn oxides are prepared via spray pyrolysis and are applied to the catalytic decomposition of hydrogen peroxide. The characteristics of the mesoporous Al–La–Mn oxides are examined using N2 adsorption, X-ray diffraction, and X-ray fluorescence measurements. The surface area and pore size of the Al–La–Mn oxides prepared via spray pyrolysis are larger than those of the Al–La–Mn oxides prepared using a precipitation method. The catalytic performance of the materials during the decomposition of hydrogen peroxide is examined in a pulse-injection reactor. It is confirmed that the mesoporous Al–La–Mn oxides prepared via spray pyrolysis exhibit higher catalytic activity and stability in the decomposition of hydrogen peroxide than Al–La–Mn oxides prepared using a conventional precipitation method.